Effect of the nitrogen-argon gas mixtures on the superconductivity properties of reactively sputtered molybdenum nitride thin films - Haberkorn, N.; Bengio, S.; Suárez, S.; Pérez, P.D.; Sirena, M.; Guimpel, J.; Haberkorn, Néstor; Guimpel, Julio (Elsevier, 2018)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina